Neck angioedema after anterior cervical discectomy and fusion with coexistent epiglottic cyst - Georgiopoulos, Miltiadis (Surg Neurol Int, 2020)
BACKGROUND: We present a case and reviewed the literature regarding airway obstruction and angioedema after an anterior cervical discectomy and fusion (ACDF). CASE DESCRIPTION: A 60-year-old female with degenerative cervical myelopathy and a previously undiagnosed epiglottic cyst underwent a C5–C6 ACDF; notably, the anesthesiologist found an epiglottic cyst when the patient was first intubated. Two hours postoperatively, the patient acutely developed severe neck swelling with airway obstruction due to angioedema. She was immediately treated with hydrocortisone and required a tracheostomy. The edema decreased markedly in the next 12 h and by the 3(rd) postoperative day it resolved. Three months later, she had no residual medical sequelae. CONCLUSION: Patients with epiglottic cysts who need cervical spine surgery should either first have the cyst treated or should be closely monitored postoperatively.